2007
DOI: 10.1002/art.22644
|View full text |Cite
|
Sign up to set email alerts
|

Specific gene expression profiles in systemic juvenile idiopathic arthritis

Abstract: Objective. Patients with systemic juvenile idiopathic arthritis (JIA) have arthritis, quotidian fevers, and other extraarticular features. This disease often remains severe and debilitating. The purpose of this study was to compare gene expression profiles in peripheral blood mononuclear cells (PBMCs) from patients with active and inactive systemic JIA to define and better understand the cause of active disease.Methods. Gene expression profiles of PBMCs were determined in cells from 9 patients with active syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
114
2
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 17 publications
12
114
2
7
Order By: Relevance
“…In this early study of nine patients with active s-JIA treated with recombinant IL-1 receptor antagonist, all of the subjects experienced a partial or complete response to treatment, further supporting the idea that IL-1 plays a key pathogenic role (19). This study contrasts slightly with others that did not find increased gene expression of IL-1β in the peripheral blood mononuclear cells of patients with s-JIA but did find upregulation of IL-1-initiated signaling pathways (14,20). Although the exact cellular source of IL-1 in s-JIA remains an open question, the clinical experience with IL-1-blocking agents, discussed below, confirms the important role of IL-1 in disease pathogenesis.…”
Section: Cytokinessupporting
confidence: 58%
See 1 more Smart Citation
“…In this early study of nine patients with active s-JIA treated with recombinant IL-1 receptor antagonist, all of the subjects experienced a partial or complete response to treatment, further supporting the idea that IL-1 plays a key pathogenic role (19). This study contrasts slightly with others that did not find increased gene expression of IL-1β in the peripheral blood mononuclear cells of patients with s-JIA but did find upregulation of IL-1-initiated signaling pathways (14,20). Although the exact cellular source of IL-1 in s-JIA remains an open question, the clinical experience with IL-1-blocking agents, discussed below, confirms the important role of IL-1 in disease pathogenesis.…”
Section: Cytokinessupporting
confidence: 58%
“…Gene expression profiles have shown increased expression of IL-6 in blood monocytes (and B-cells) in patients with active s-JIA compared with the expression in healthy controls (14). Additionally, serum IL-6 levels are significantly elevated in s-JIA patients compared with the same in healthy, age-matched controls.…”
Section: Cytokinesmentioning
confidence: 99%
“…Gene expression studies have also provided additional evidence that the role of the adaptive immune system is rather limited in systemic JIA as compared with the other JIA subtypes, whereas the contribution of the innate immunity may be much more prominent (19,25,26). Several recent gene expression (microarray) studies, for example, have shown that systemic JIA can be distinguished from other subtypes of JIA by the presence of an up-regulation of the innate immune pathways, including interleukin-6, Toll-like receptor/ interleukin-1 receptor, as well as a down-regulation of the gene networks involving T cell-related and MHCrelated biologic processes, including antigen presentation (19).…”
Section: Potential For Improved Treatment Decisions and Outcomes In Jiamentioning
confidence: 99%
“…The innate immune system is believed to play an important role. An expansion of cells of monocyte/macrophage lineage during SJIA flare (9)(10)(11), with increased expression of corresponding genes, has been reported (8,9,(12)(13)(14). Crosstalk between the innate and adaptive immune system regulates a healthy inflammatory response.…”
mentioning
confidence: 99%